PERAN GURU DALAM MENGEMBANGKAN SIKAP PEDULI LINGKUNGAN PADA SISWA DI SDN 005 SAMARINDA ULU - Oktaviani, Siska; Yulista Timu, Patrisia (SISTEMA: Jurnal Pendidikan, 2024)
This research aims to determine the role of teachers in developing students' environmental care attitudes in class II at SDN 005 Samarinda Ulu. Attitudes that care about the environment include cleaning classrooms, participating in Clean Friday activities. Character education includes love for the environment. Environmental concern includes cleaning the school environment. The purpose of this research is to determine the role of teachers in developing environmentally caring attitudes. This type of research uses qualitative research. Research subjects were class teachers, students, environmental coordinator teachers at SDN 005 Samarinda Ulu. Data collection techniques and instruments in this research are interviews, documentation. In testing the validity of the data using source triangulation. The results of research on teachers, students and environmental coordinator teachers show that concern for the environment at SDN 005 Samarinda Ulu is quite good in terms of maintaining the classroom environment and the environment around the school, the role of teachers in maintaining environmental cleanliness as leaders and motivators. It can be concluded that the role of teachers in developing environmentally caring attitudes is very influential in cultivating environmentally caring character. Keywords: teacher's role, environmental care, elementary school